Domniemane i rzeczywiste przyczyny chińskiego cudu gospodarczego. Polemika z Kazimierzem Poznańskim - Rotengruber, Przemysław (Człowiek i Społeczeństwo, 2018)
Domniemane i rzeczywiste przyczyny chińskiego cudu gospodarczego. Polemika z Kazimierzem Poznańskim [Alleged and real reasons for the Chinese economy miracle. A polemic with Kazimierz Poznański] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 67–84, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. China has come a long way in the last hundred years. It is so long that it’s easy to forget about the problems that the Chinese had to face earlier. They struggled with patterns of long duration making it difficult for them to break out of the centuries-old stagnation. The Chinese were looking for new patterns of political culture. However, not only those patterns required a correction. If Fukuyama is right, the rules of caring for one’s family at the expense of social obligations have turned out to be no less troublesome. The Chinese way to prosperity led then not only through the public sphere, but also through the hearts and minds of the Chinese. They had to cut themselves off from the past. Meanwhile, in the time of economic prosperity, the longing for the past returns. The place of doctrines borrowed from the Western world replaces nostalgia. Deng Xiaoping’s political references to the teachings of Confucius are – in the blink of an eye – becoming the basic message. It is not surprising that the Chinese people want to forget about the embarrassing moments of their own history. These trends, however, should not affect external observers of economic life in China. One of such observers is Kazimierz Poznański. He believes that the cause of the Chinese economic miracle is the Confucian ethics (despite the historical changes shaping the Chinese mentality). The aim of the article is to verify this hypothesis.